2005
DOI: 10.1007/s10142-005-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the embryo transcriptome of hexaploid winter wheat (Triticum aestivum cv. Mercia) during maturation and germination

Abstract: Grain dormancy and germination are areas of biology that are of considerable interest to the cereal community. We have used a 9,155-feature wheat unigene cDNA microarray resource to investigate changes in the wheat embryo transcriptome during late grain development and maturation and during the first 48 h of postimbibition germination. In the embryo 392 mRNAs accumulated by twofold or greater over the time course from 21 days postanthesis (dpa) to 40 dpa and on through 1 and 2 days postgermination. These inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 53 publications
2
33
1
Order By: Relevance
“…Several transcriptomic analyses on seed development and germination have been reported in wheat and barley (Hordeum vulgare; Wilson et al, 2005;Sreenivasulu et al, 2008;Wan et al, 2008). Numerous transcriptome analyses have examined expression profiles during seed development and germination in Arabidopsis thaliana.…”
Section: Introductionmentioning
confidence: 99%
“…Several transcriptomic analyses on seed development and germination have been reported in wheat and barley (Hordeum vulgare; Wilson et al, 2005;Sreenivasulu et al, 2008;Wan et al, 2008). Numerous transcriptome analyses have examined expression profiles during seed development and germination in Arabidopsis thaliana.…”
Section: Introductionmentioning
confidence: 99%
“…While some transcriptome studies in wheat (Triticum aestivum) and barley have been performed (Watson and Henry, 2005;Wilson et al, 2005;Sreenivasulu et al, 2008), the lack of complete genome sequence data prevents comprehensive whole transcriptome analysis, including promoter analysis once coexpressed gene sets have been identified. For example, the most comprehensive transcriptome study in monocots to date, using barley (Sreenivasulu et al, 2008), reported that cis element searches were performed in homologous rice (Oryza sativa) promoters, as this sequence information is not yet available for barley.…”
mentioning
confidence: 99%
“…In wheat, the highest expression level of the VP1 gene is observed at about 50 DAP, later on -in the ripening stage (60 DAP)-it drops down (Utsugi et al, 2008). However, Wilson et al (2005) found that the expression of the VP1 gene peaked about 21 DAP, and at further stages, until 40 DAP, decreased. In our experiments in both examined cultivars, two peaks of the VP1 gene expression were observed.…”
Section: Discussionmentioning
confidence: 92%